Short-term Impacts of Secondary Postpartum Haemorrhage on Maternal Health - Faizah, Mabruka; Akther, Nasreen; Choudhury, Shahana Ferdous; Azam, Iffana; Chowdhury, Fatama Tul Tanzina; Mohammad , Nurunnabi (Journal of Monno Medical College, 2025)
Background: Postpartum haemorrhage (PPH) is unpredictable and potentially catastrophic, occurring even in women considered being at low risk. PPH endures as a significant cause of maternal morbidity and mortality in low- and middle-income countries (LMICs). Objective: The purpose of the present study was to observe the short-term effects of secondary postpartum hemorrhage on maternal health. Methodology: This hospital-based cross-sectional study was conducted involving 40 purposively selected women aged 18 years and older who were diagnosed with secondary PPH and admitted more than 24 hours after childbirth or during the puerperal period. These women were interviewed using a pre-tested semi-structured questionnaire in the purposively selected Department of Obstetrics and Gynecology at Sylhet MAG Osmani Medical College Hospital in Bangladesh. Results: Secondary PPH was significantly more common in the 26–35 age group (67.5%) compared to those aged 25 years or younger (32.5%). Among the women studied, 22.5% were primipara and 77.5% were multiparas, with secondary PPH occurring significantly more frequently in multipara women. A notable proportion of patients (70%) presented with varying degrees of anemia. Retained placental fragments were identified as the primary cause of secondary PPH in 52.5% of cases, followed by endometritis and sub-involution, each accounting for 15%. More than half of the patients (57.5%) required blood transfusions based on the severity of their anemia, and 30% of those with secondary PPH had hospital stays that exceeded 5 days. Conclusion: Despite extensive collaborative efforts at all levels, implementation and adherence to recommended management practices for postpartum hemorrhage in obstetric emergencies remain insufficient. Journal of Monno Medical College December, 2024;10 (2):83-88